2020
DOI: 10.1002/leg3.33
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐leafed lupin (Lupinus angustifolius L.) β‐conglutin: A multifunctional family of proteins with roles in plant defence, human health benefits, and potential uses as functional food

Abstract: Lupinus angustifolius or narrow-leafed lupin (NLL) is an important Pulse world-wide and an outstanding alternative source of high quality proteins. NLL β-conglutin (vicilin or 7S acid globulin), a multigene family of proteins, is the main representative protein in NLL seeds exhibiting multifunctional properties and benefits recently discovered.These functions may result from specific structural features of NLL β-conglutins in comparison with most legume vicilin proteins. From the agricultural side, NLL β-congl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
(77 reference statements)
0
20
0
Order By: Relevance
“…This region-consisting of 8-10 α-helicesis known as the mobile N-terminal arm, which has been also shown to embrace the largest structural variability of the seven NLL β-conglutins (33). It has been suggested that the putative functional differences of the β-conglutin isoforms can be related to these structural differences (9). In the γ1-conglutin the peptide sequences that were identifiable across more than 40 lines were found within the 269-430 residues that correlates with the TAXi-C domain position within this protein (Figure 1D).…”
Section: Evaluation Of Conglutin Protein Sequence Conservation Across...mentioning
confidence: 99%
See 1 more Smart Citation
“…This region-consisting of 8-10 α-helicesis known as the mobile N-terminal arm, which has been also shown to embrace the largest structural variability of the seven NLL β-conglutins (33). It has been suggested that the putative functional differences of the β-conglutin isoforms can be related to these structural differences (9). In the γ1-conglutin the peptide sequences that were identifiable across more than 40 lines were found within the 269-430 residues that correlates with the TAXi-C domain position within this protein (Figure 1D).…”
Section: Evaluation Of Conglutin Protein Sequence Conservation Across...mentioning
confidence: 99%
“…These proteins have been classified into four major families: α-, β-, γ-, and δconglutins, which comprise three, seven, two, and four subfamilies, respectively (7). Distinct nutritional and nutraceutical properties have been attributed to each conglutin family; for example, the γconglutins are known to have blood glucose lowering effects (8), whilst β-conglutin proteins-which have demonstrated antiinflammatory and antioxidant activities-are reported as the major proteins responsible for lupin allergy (9). Hence, variation in abundance of these proteins across different lupin varieties can impact their nutritional quality and bioactive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that conglutins β1, β3 and β6, main types of reserve proteins in Lupinus angustifolius seeds, present antioxidant activity, among other health benefits [6], are capable of reducing the expression of pro-inflammatory cytokines IL-1β, IL-2, IL-6, IL-8, IL-12, IL-17, TNF-α and IFNγ, in addition to decreasing the levels of NF-κB, NO and iNOS, which can make its consumption adequate in the treatment of certain pathologies. In pancreatic cells, these conglutins also reduce the expression levels of chemotactic factors as CCR2 and CCL5, improving the inflammatory state by inhibiting the recruitment and migration of immune cells [7].…”
Section: Antioxidants and Anti-inflammatory Compoundsmentioning
confidence: 99%
“…Current Advances Research in Nutraceutical Compounds of Legumes, Pseudocereals and Cereals DOI: http://dx.doi.org/10.5772/intechopen.97782 Interestingly, Lupinus angustifolius seed conglutins β1, β3, and β6 are capable of acting positively against diabetes [13]. This activity is mediated by its antioxidant and regulatory activities by (i) increased cellular glucose uptake, (ii) positive regulation of IRS-1, GLUT-4 and increased protein synthesis of p85-PI3K, (iii) activation of IRS-Q/PI-3-KINASE, which activates other components of the signalling cascade, (iv) reduction of oxidative stress reducing the level of protein carbonylation and increasing glutathione levels GSH and decreasing the antioxidant activity of SOD and catalase enzymes, (v) reduction in NO production levels, (vi) increased glucose catabolism, increasing the expression of, among others, hexokinase and decreasing that of GSK3β [6,14]. Furthermore, the already described anti-inflammatory activity of these conglutins β could also help in the treatment of diabetes by reducing the inflammation of the pancreatic islets [7].…”
Section: Metabolic Syndrome: Diabetes Obesity and Cardiovascular Diseasesmentioning
confidence: 99%
“…Albumins, globulins, prolamin, and glutelin are the major SSPs found in the moth bean [ 11 ]. Vicilins (legume lectin) are 7S globulins found in abundance as reserves in seeds of leguminous and non-leguminous plants, representing as much as 70 to 80% of total protein in Vigna unguiculata , Vigna radiata , Glycine max , Phaseolus vulgaris , Canavalia ensiformis , Lupinus albus and Vigna aconitifolia [ 12 , 13 ]. Vicilin is characterized as trimeric oligomers of 150–170 kDa formed by three similar subunits of 40–70 kDa with no disulfide linkages [ 14 ].…”
Section: Introductionmentioning
confidence: 99%